In-hospital mortality and its determinant factors among patients with sepsis - Fadrian, Fadrian; Decroli, Eva; Ahmad, Armen; Kam, Alexander; Muharramah, Disa Hijratul; Pradana, Genta; Putri, Vidola Yasena (Universa Medicina, 2025)
BACKGROUNDSepsis is a heterogeneous syndrome characterized by a variety of clinical features. Multiple studies have identified sepsis as the leading cause of death in hospitalized patients. A comprehensive report on the incidence, clinical characteristics, and predictors of sepsis is important. This study aimed to determine the relative importance of predictors of in-hospital mortality in sepsis. METHODSA retrospective cohort study at Dr. M. Djamil Central General Hospital focused on sepsis patients. A total of 200 participants, aged 18 and older, were included based on specific criteria and recruited through consecutive sampling. Data was gathered from medical records and laboratory results to identify factors influencing mortality in sepsis patients. These factors were classified into sociodemographic, intrinsic, and extrinsic categories. Statistical analysis utilized simple and multiple logistic regression. A p-value of less than 0.05 indicated statistical significance for predicting in-hospital mortality in sepsis. RESULTSThe sepsis patient mortality rate was 69.50%. Hospital-acquired pneumonia (HAP) emerged as the most common infectious diagnosis, impacting 47.50% of the patients. Type 2 diabetes mellitus (Type 2 DM) was identified as the most frequent comorbidity, present in 36.50% of cases. Multivariate analysis indicated that HAP (adjusted odds ratio [aOR] 2.32; 95% confidence interval [CI] 1.19–4.49; p=0.013) and hyperlactatemia (aOR 2.11; 95% CI 1.06–4.18; p=0.032) significantly increased the risk of mortality in sepsis patients. CONCLUSIONHospital-acquired pneumonia was the primary predictor of mortality in sepsis patients. Timely prediction and evaluation of sepsis outcomes are essential for developing strategies to reduce mortality rates.